2002
DOI: 10.1046/j.1439-0418.2002.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors of between‐ and within‐plant distribution of Metopolophium dirhodum (Hom., Aphididae) on small grain cereals

Abstract: The relationship between abundance of rose‐grain aphid Metopolophium dirhodum (Walker) and leaf chlorophyll content of spring wheat, spring oats and winter barley was investigated. Within production stands of each crop 18–25 plots were established, located at places with different plant quality where aphids were counted on particular leaves of 50–100 tillers, and the leaf chlorophyll content and area were determined. In all stands aphid numbers × tiller−1 increased exponentially with chlorophyll content (r2 = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Metopolophium dirhodum is a leaf‐feeding aphid (Watt, 1979) and a positive response to resource allocation to the leaves and stem can therefore be expected. Honek (1991b) and Honek and Martinkova (2002) found that M. dirhodum numbers are higher on wheat and barley with bigger leaves and Honek (1991a) attributed increased number of M . dirhodum after fertilizer application to changes in barley morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metopolophium dirhodum is a leaf‐feeding aphid (Watt, 1979) and a positive response to resource allocation to the leaves and stem can therefore be expected. Honek (1991b) and Honek and Martinkova (2002) found that M. dirhodum numbers are higher on wheat and barley with bigger leaves and Honek (1991a) attributed increased number of M . dirhodum after fertilizer application to changes in barley morphology.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship was not found in the present study, in which yellowness and aphid abundance were negatively correlated, suggesting that aphids are attracted to less suitable plants. Many factors other than those important in host selection determine aphid populations, including the nutritional quality of the host (Bado et al , 2002; Honek & Martinkova, 2002). Two factors that influence host nutritional quality include chlorophyll and nitrogen (Weibull, 1987; Honek & Martinkova, 2002), a major component of chlorophyll (Fox et al , 1994), and would make leaves appear more green and explain why higher aphid populations are found on plants with a lower attractivity index in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although cereal aphids are important pests ( Vickerman and Wratten 1979 , Dixon 1987 , Dedryver et al 2010 ), M. dirhodum , in our opinion, has not aroused the attention it deserves due to its abundance. This is because M. dirhodum colonizes only leaves ( Honek 1987 , Honek and Martinkova 2002 ), and more attention is paid to aphids colonizing ears, because they are likely to cause more damage ( Wetzel 2004 ). Nevertheless, its economic importance is well documented in countries where M. dirhodum is abundant, North America ( Johnston and Bishop 1987 , Schotzko and Bosque-Perez 2000 , Clement et al 2004 ), South America ( Lopes-da-Silva and Vieira 2007 , Sepulveda et al 2017 ), and Central Europe ( Havlickova 1997 ).…”
mentioning
confidence: 99%
“…The positive response shown by aphids to nitrogen fertiliser in particular is thought to be due to the improved nutritional quality of the host plant amino acid profile (Weibull 1987;Awmack and Leather 2002), which can promote aphid growth and fecundity (Ponder and others 2000;Khan and Port 2008). Indirect effects of soil fertility on cereal aphids, mediated through effects on host morphology and attractiveness, are also apparent (Honě k and Martinková 2002;Garratt and others 2010b). Therefore, fertiliser application can result in higher population densities of cereal aphids (Hasken and Poehling 1995;Wang and others 2015;Zhao and others 2015) with consequent effects on crop damage, virus transmission and yields (van Emden and Harrington 2017).…”
Section: Introductionmentioning
confidence: 99%